Comparison between the force application point determined by portable force plate system and the center of pressure determined by pressure insole system during alpine skiing - Nakazato, K.; Scheiber, P.; Müller, E. (Sports Engineering, 2013)
The purposes of this study were (1) to compare the force application point (FAP) calculated by a portable force plate system and the center of pressure (COP) calculated by a pressure insole system during alpine skiing, and (2) to assess whether any statistical differences between FAP/COP characteristics were influenced by the skiing modes, skiers` skill levels, or pitch of the slope. Seven expert and eight intermediate skiers performed 20 double turns with two different skiing techniques. Similarities between the time characteristics of both systems and repeated measures ANOVA were used for the statistical analysis. Time characteristics of both systems in the y direction (anterior-posterior) were highly comparable. The mean FAP and COP in the x direction (medial-lateral) were different in all skiing modes for the outer ski and for the inner ski for the expert skiers. The ranges of the FAP in both directions were greater than the COP in almost all conditions.